Hubungan Albuminuria dengan Silent Myocardial Ischemia dan Keterlambatan Heart Rate Recovery pada Subjek Pria Hipertensi Tanpa Diabetes Melitus - Johan Winata; A. Lucia Panda; R. Abd Azis (Jurnal Kardiologi Indonesia, 2015)
Background: Silent myocardial ischemia (SMI) defined asmyocardial ischemiawithout anginal pain. SMI is frequently found in diabetes due to autonomic neuropathy, but in hypertension the involvement of autonomic neuropathy is still not known. Heart rate recovery(HRR) has been known as manifestation of autonomic neuropathy.The simple measurement of HRR is potential as screening tools for autonomic neuropathy. Nevertheless, SMI and delayed HRR are known as independent predictors for cardiovasluar mortality, hence emphasize the importance for early diagnosis. In diabetes, albuminuria has been proven to be an independent predictor for SMI and delayed HRR, but in hypertensive patients without diabetes the correlation is still unclear.Objectives: This study is aimed to determine the incidence of SMI, delayed HRR, and albuminuria in hypertensive patients without diabetes, the correlation between albuminuria and SMI and delayed HRR.Methods: This is an observational study with cross-sectional approach. Fourty consecutive hypertensive without diabetes, history of chest pain, and known CAD. They underwent treadmill exercise testing with collection of spot urine before exercise to measure albumin urine to creatinine ratio (ACR). SMI and HRR to 3 minutes were then recorded.Results: SMI was diagnosed in 15% patients. The incidence of delayed HRR in the first, second and third minute after peak exercise were 60%,80%, and52.5% respectively. Albuminuria was significantly associated with SMI (OR 13.889 (1.423 – 135.544), p = 0.014). There were no signification correlation between albuminuria and delayed HRRConclusion: Albuminuria is a good predictor for SMI in hypertensive patients.